Les Périples de Kalila et Dimna The Journeys of Kalila and Dimna: Itineraries of Fables in the Arts and Literature of the Islamic World - Brac de la Perrière, Eloïse 1972- (Brill Studies in Middle Eastern Literatures Ser., 2022)
This book marks a major contribution to the study of Arabic illustrated manuscripts of Kalīla wa-Dimna and its Persian and Ottoman versions. The studies gathered in this volume showcase a wide diversity of approaches crossing textual investigation, codicological and iconographic study, and laboratory analysis. Ce livre constitue une contribution majeure à l'étude des manuscrits arabes illustrés de Kalīla wa-Dimna et de ses versions persane et ottomane. Les articles rassemblés dans ce volume montrent une grande diversité d'approches, croisant investigation textuelle, étude codicologique et iconographique et analyses physico-chimiques.